2010
DOI: 10.1089/oli.2010.0230
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin-Containing Polymer Delivery System for Light-Directed siRNA Gene Silencing

Abstract: In this study, we have investigated the possibility of combining a cyclodextrin-containing polymer (CDP) with siRNA molecules to modulate gene expression in a light-directed manner through photochemical internalization (PCI) technology. We utilized S100A4 as a model gene to evaluate the efficacy of gene silencing. After optimization of carrier/cargo ratio and illumination dose, real-time reverse transcriptase-polymerase chain reaction data showed between 80% and 90% silencing in the siRNA samples treated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Hovig et al co-delivered cationic β-cyclodextrin-containing polymers with photosensitizer additives, which initiate photochemical endosomal and lysosomal membrane damage, to enhance the release and delivery of siRNA into osteosarcoma and melanoma cell lines. They found an 80% increase in gene silencing after exposure to 420 nm visible light, attributing siRNA release to endosomal/lysosomal escape . Liu et al was able to show a similar result by using photosensitizers to increase endosomal/lysosomal escape and DNA unpacking using OEI-based polymers conjugated with an aminoacrylate linker; this system was readily cleaved within the polymer backbone using visible light initiation (Figure B) .…”
Section: Chemical Design Of Polymeric Cationic Vectorsmentioning
confidence: 81%
See 1 more Smart Citation
“…Hovig et al co-delivered cationic β-cyclodextrin-containing polymers with photosensitizer additives, which initiate photochemical endosomal and lysosomal membrane damage, to enhance the release and delivery of siRNA into osteosarcoma and melanoma cell lines. They found an 80% increase in gene silencing after exposure to 420 nm visible light, attributing siRNA release to endosomal/lysosomal escape . Liu et al was able to show a similar result by using photosensitizers to increase endosomal/lysosomal escape and DNA unpacking using OEI-based polymers conjugated with an aminoacrylate linker; this system was readily cleaved within the polymer backbone using visible light initiation (Figure B) .…”
Section: Chemical Design Of Polymeric Cationic Vectorsmentioning
confidence: 81%
“…They found an 80% increase in gene silencing after exposure to 420 nm visible light, attributing siRNA release to endosomal/lysosomal escape. 769 Liu et al was able to show a similar result by using photosensitizers to increase endosomal/lysosomal escape and DNA unpacking using OEI-based polymers conjugated with an aminoacrylate linker; this system was readily cleaved within the polymer backbone using visible light initiation (Figure 33B). 762 With the use of jetPRIME® as the polymeric delivery vector, Takishima et al was able to show that a preliminary exposure of cells to blue light inhibited the delivery of pDNA complexes, while unexposed areas still resulted in an uptake in HeLa, HEK293, and HepG2 cell lines.…”
Section: Incorporating Stimuli-responsive Propertiesmentioning
confidence: 84%
“…Importantly it is also capable of producing light-directed delivery of siRNA into the tissue of interest. Bøe et al (2010) demonstrated the utilization of PCI-mediated light-directed delivery of CDP-siRNA complex. Optimization of carrier/cargo ratio and illumination dose provided 80% and 90% silencing in the siRNA samples treated with PCI compared with untreated control.…”
Section: Chitosanmentioning
confidence: 99%
“…Further studies on using PCI for oligonucleotide mediated gene expression silencing have been performed with siRNA in combination with a variety of delivery vehicles. Thus, Bøe and co-workers showed good effects of PCI with siRNA with polymeric vehicles such as polyethylenimine [164], cyclodextrin-containing polymers [165], peptides [166] and polyamidoamine (PAMAM) carriers [167]; as well as with some, but not all of the tested lipid vehicles [164]. In case of PAMAM dendrimer complexed the authors tested several generations (0-7) of PAMAM dendrimers complexated with both a GFP siRNA and a GFP mRNA with regard to their PCI-mediated gene modulation efficiency in OHS-EGFP and OHS osteosarcoma cells respectively.…”
Section: Pci Mediated Oligonucleotide Deliverymentioning
confidence: 99%